Wasatiyah Optimization in Sustainable Wealth Management (Journal of Economics, Law and Society, 2025)
Wealth generation and management are pivotal for sustainability. This paper explores the crucial role of wealth management in achieving regenerative sustainability, advocating for wealth optimization over maximization.  It introduces a novel framework for Islamic Wealth Management (IWM) centered on regenerative and sustainable wealth creation, guided by the Islamic principle of Wasatiyah (moderation). This framework aims to integrate financial success with ethical responsibilities and spiritual well-being.  A key innovation is the Normalized Balance Coordinates (NBCs), a generalized, unified measure applicable to various contexts involving tensions and trade-offs.  The NBCs, initially conceived as Normalized Wasatiyah Coordinates (NWCs) for IWM, employ a two-dimensional Cartesian system with axes normalized between -1 and 1. This system provides a unified measure of performance across competing priorities, such as economic growth vs. balance of natural systems, efficiency vs. equity, quality vs. quantity, and full employment vs. price stability.  In the context of IWM, the NBCs assess both ethical and financial performance, where positive coordinates reflect adherence to Wasatiyah principles, while negative coordinates highlight areas for improvement. The paper outlines regenerative transition strategies for each quadrant, using Substitutions, Transformations, and Offsets (STOs) to guide decision-makers through diverse situations. By integrating ethical considerations with financial strategies (or, more broadly, balancing competing priorities), the NBCs framework offers a holistic model that views wealth (or any resource under consideration) as a sacred trust with inherent social, environmental, and spiritual dimensions. The paper concludes by emphasizing the transformative potential of the NBCs approach in promoting holistic balancing optimization, as opposed to singular maximization, and fostering a more equitable, sustainable, and ethically grounded global system.